Resistance in wheat genotypes to rice (Oryza sativa) weevil (Sitophilus oryzae) - JHA, A N; SRIVASTAVA, CHITRA; DHAR, SHIVA (The Indian Journal of Agricultural Sciences, 2013)
Eight promising cultivars of wheat, viz. WH 542, WH 896, DDW12, PDW291(d), PDW239, PBW343, HI 8381(d) and C306 were evaluated against the infestation of Sitophilus oryzae (L.) after 90 days of storage condition. The maximum per cent grain loss (45.6), weight loss (18.28) and number of insect emerged (57.6) were recorded in HI 8381(d). However, the minimum percent weight loss and number of insects emerged were 4.88 and 13.33, respectively in C306. The minimum per cent grain loss (18.0) was recorded in DDW Statistically the per cent grain loss and percent weight loss were found to be not significant. The findings from this study suggest that the varieties DDW 12 and C 306 are best for field as well as storage condition.